Factors Associated with the Incidence of Anemia in Pregnancy: Scoping Review - Shalma, Avriana Faiza; Agustia, Nency (Journal of Health, Medicine and Nursing, 2024)
Anemia during pregnancy is a prevalent condition with significant implications for maternal and fetal health, posing public health challenges in various countries. This scoping review aims to identify and synthesize the factors associated with the incidence of anemia among pregnant women, examining biological, behavioral, and socio-economic influences. A systematic search was conducted across multiple databases, focusing on studies published in the last decade that address the prevalence and determinants of anemia in pregnancy. The findings indicate that anemia in pregnancy is associated with a range of factors, including nutritional deficiencies (particularly iron, folic acid, and vitamin B12), maternal age, parity, and pre-existing health conditions such as malaria and intestinal infections. Additionally, socio-economic factors such as low income, limited education, and inadequate access to healthcare services further exacerbate the risk of anemia. Behavioral aspects, including dietary habits and prenatal care adherence, also play a critical role. This review highlights the need for comprehensive strategies that integrate nutritional interventions, health education, and improved healthcare access to address the multifaceted causes of anemia in pregnancy. By understanding these factors, health policymakers and practitioners can develop targeted interventions to reduce the incidence of anemia among pregnant women, ultimately improving maternal and child health outcomes.